PENGARUH PERSEPSI SISWA MENGENAI MEDIA ANIMASI SIMULASI FISIKA TERHADAP HASIL BELAJAR SISWA - Alex Chandra; I Dewa Putu Nyeneng; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
Perception student is the perspective student to an object. on this research it is learning media. While the learning media is an important tool in learning a lesson. Current media usage has grown with the Technology Information and Communi-cation who gave birth media based computer, so it is necessary to develop media animation simulation. This research is done at SMA Persada Bandar Lampung, using a class that X.1 class with a sample population of 35 students from the class X. This research to determine the effect of perceptions student about media animation physics simulation to result learning. This research data perception students regarding media animation simulation physics used questionnaires completed by the students and the students have calculated the value of the end. As for the data result learning obtained from the test in the form of multiple choice questions that have been recapitulated in value. Then to examine the effect of the normality test, linearity, correlation and simple linear regression. Results of research based on the analysis of hypothesis testing are a very strong effect perception student about media animation simulation physics to result learning with the value of r is 0.996 with a positive direction and the regression equation is Y = 7.858 + 0.939 X on the material in class X.1 at SMA Persada Bandar Lampung. Key word: Student perception, media animations simulated , and Result Studying